Peningkatan Hasil Belajar IPA Materi Senyawa Menggunakan Model Tgt (Team Games Turnament) Kelas VIII SMPN 2 Sumber - Qoimatu Dinillah; Nurwanti Fatnah; Teti Herawati (LPPM Institut Pendidikan Nusantara Global, 2025)
This research investigated the efficacy of the Team Games Tournament (TGT) learning model in enhancing the learning outcomes of eighth-grade students (Class VIII E) at SMPN 2 Sumber in the subject of Natural Sciences (IPA), specifically focusing on the topic of chemical compounds. The study was motivated by observed low levels of student engagement and the prevalence of conventional instructional methods in teaching chemical compounds, a subject often perceived as abstract and challenging for a subset of learners. This situation potentially contributes to diminished overall achievement in Science. A Classroom Action Research (CAR) design, following the cyclical framework proposed by Kemmis and McTaggart, was employed. The research was conducted across two iterative cycles, each encompassing the phases of planning, action implementation, observation, and reflection. The participant sample comprised 37 students. Data were collected through systematic observation, summative tests, and relevant documentation, subsequently subjected to descriptive quantitative analysis. The findings revealed a statistically significant improvement in student learning outcomes pertaining to chemical compounds following the implementation of the TGT learning model. In the pre-cycle phase, only 22% of students achieved scores exceeding the established Learning Objectives Achievement Criteria (KKTP), with a mean score of 53,91. Subsequent to the intervention, the first cycle demonstrated an increase to 68% of students achieving mastery, with a corresponding mean score of 74,59. A more substantial improvement was evident in the second cycle, where 89% of students attained mastery, and the mean score reached 86,05. These increments suggest that the TGT learning model is an effective pedagogical strategy for fostering enhanced comprehension and improved learning outcomes in the context of teaching chemical compounds. Consequently, the TGT learning model presents a viable and engaging alternative for Science instruction, with the potential to significantly elevate student academic achievement.